Emergence of anthropogenic warming in Antarctica - Zihuan Zhang; Sai Wang; Deliang Chen; Tingfeng Dou; Cunde Xiao; Annette Rinke; Shoudong Zhao; Petra Heil; Wen Chen; Minghu Ding (Science Bulletin, 2026)

RouteView 2.0: A real-time operational planning system for vessels on the Arctic Northeast Passage - Adan Wu; Tao Che; Jinlei Chen; Xiaowen Zhu; Qingchao Xu; Tingfeng Dou; Rui Zhang; Shengpeng Chen; Jiping Wang; Yongfan Guo (Environmental Modelling & Software, 2025)

Characteristics of methane and carbon dioxide in ice caves at a high-mountain glacier of China - Zhiheng Du; Hao Cui; Lei Wang; Fangping Yan; Yushuo Liu; Qian Xu; Simin Xie; Tingfeng Dou; Yanzhao Li; Pengfei Liu; Xiang Qin; Cunde Xiao (Science of The Total Environment, 2024)

On the Shallowing of Antarctic Low-Level Temperature Inversions Projected by CESM-LE under RCP8.5 - Minghu Ding; Lin Zhang; Tingfeng Dou; Yi Huang; Yingyan Luo; Junmei Lyu; Cunde Xiao (Journal of Meteorological Research, 2024)

A Statistical Linkage between Extreme Cold Wave Events in Southern China and Sea Ice Extent in the Barents-Kara Seas from 1289 to 2017 - Cunde Xiao; Qi Zhang; Jiao Yang; Zhiheng Du; Minghu Ding; Tingfeng Dou; Binhe Luo (Advances in Atmospheric Sciences, 2023)

On the drivers of temperature extremes on the Antarctic Peninsula during austral summer - Sai Wang; Minghu Ding; Ge Liu; Ting Wei; Wenqian Zhang; Wen Chen; Tingfeng Dou; Cunde Xiao (Climate Dynamics, 2022)

A Preliminary Investigation of Arctic Sea Ice Negative Freeboard from in-situ Observations and Radar Altimetry - Shutong Li; Tingfeng Dou; Cunde Xiao (Journal of Ocean University of China, 2021)

Extreme sea levels along coastal China: uncertainties and implications - Jiayi Fang; Thomas Wahl; Qiang Zhang; Sanne Muis; Pan Hu; Jian Fang; Shiqiang Du; Tingfeng Dou; Peijun Shi (Stochastic Environmental Research and Risk Assessment, 2021)
Extreme sea levels (ESLs) due to typhoon-induced storm surge threaten the societal security of densely populated coastal China. Uncertainty in extreme value analysis (EVA) for ESL estimation has large implications for coastal communities’ adaptation to natural hazards. Here we evaluate uncertainties in ESL estimation and relevant driving factors based on hourly observations from 13 tide gauge stations and a complementary dataset derived from a hydrodynamic model. Results indicate significant uncertainties in ESL estimations stemming from using different EVA methods, which then propagate to the inundation assessment. Amplification factors due to sea-level rise (SLR) are highly sensitive to local relative SLR and the shape of the exceedance probability curve, which in turn depends on the selected EVA method. The hydrodynamic model hindcast indicates that high ESLs mainly occurred in eastern coastal China due to typhoon-induced storm surge. Larger uncertainties in the modelled ESLs are found for the coasts of the Yangtze River Delta, and particularly in the river mouth region. Future research and adaptation planning should prioritize these regions given expected future rising sea level, compound flood events, and human-induced factors (e.g. subsidence). This study provides theoretical and practical references for adaptation to ESL-related hazards along coastal China, with implications for coastal regions worldwide.

Reconstruction of autumn sea ice extent changes since AD1289 in the Barents-Kara Sea, Arctic - Qi Zhang; Cunde Xiao; Minghu Ding; Tingfeng Dou (Science China Earth Sciences, 2018)

Changes in the Proportion of Precipitation Occurring as Rain in Northern Canada during Spring–Summer from 1979–2015 - Wei Han; Cunde Xiao; Tingfeng Dou; Minghu Ding (Advances in Atmospheric Sciences, 2018)